2005
DOI: 10.1152/ajpcell.00099.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pro-Muclin in pancreatic AR42J cells induces functional regulated secretory granules

Abstract: It is not clear how protein cargo is sorted to and retained in forming regulated secretory granules (RSG). Here, the sulfated mucin-type glycoprotein pro-Muclin was tested for its ability to induce RSG in the poorly differentiated rat pancreatic cell line AR42J. AR42J cells express RSG content proteins, but they fail to make granules. Adenovirus-pro-Muclin-infected AR42J cells store amylase, accumulate RSG, and respond to hormonal stimulation by secreting the stored protein. Expression of pro-Muclin combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…We suggested that Muclin is important in protein sorting and packaging in the regulated secretory pathway of the acinar cell (4,9). We also showed that when Muclin was expressed in AR42J cells that lack the regulated pathway, the cells developed granules whose secretion could be stimulated by caerulein (11).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…We suggested that Muclin is important in protein sorting and packaging in the regulated secretory pathway of the acinar cell (4,9). We also showed that when Muclin was expressed in AR42J cells that lack the regulated pathway, the cells developed granules whose secretion could be stimulated by caerulein (11).…”
Section: Discussionmentioning
confidence: 70%
“…We have previously shown that ectopic expression of Muclin in the rat pancreatic exocrine cell line AR42J induces functional regulated secretory granules (11). Along with the decrease in stimulated amylase release from Muclin-deficient acini, this indicates an important role of Muclin in the formation of zymogen granules.…”
Section: Protein Traffic In the Regulated Secretory Pathway Is Alterementioning
confidence: 84%
See 3 more Smart Citations